The Actualization of The Economic Movement: An Approach to The Study of Economic Growth in Indonesia - Rahmat Saleh; Nurafifah Wulandari (Universitas Nusantara PGRI Kediri, 2024)
An indication of the success of a country's economic development is important to the attention of various parties. The potential gap in economic growth inequality between regions often occurs, sometimes in line with and sometimes not along with improvements in human development and other financial aspects. The purpose of our research is to identify the effect of Regional Original Revenue (PAD) and Human Development Index (HDI) on economic growth (GRDP). The data used in this study are secondary. The use of secondary data obtained from government agencies in the provincial and national environment, namely the Central Statistics Agency, in the form of panel data before the COVID-19 pandemic from 34 provinces in Indonesia for four years, 136 data observations applying regression analysis with Eviews 25 analysis tools in the form of panel data models pooling least square (PLS) / common effect, random effect and fixed effect. The results found that PAD partially affects GRDP while HDI has no significant effect on economic growth. Even though simultaneously the influence of PAD and HDI on economic growth is 73%, it is indicated by the results of the coefficient of determination R-square.